Climate Change Increases the Severity and Duration of Soil Water Stress in the Temperate Forest of Eastern North America - Cholet, Cybèle; Houle, Daniel; Sylvain, Jean-Daniel; Doyon, Frédérik; Maheu, Audrey (Frontiers in Forests and Global Change, 2022)
Under climate change, drought conditions are projected to intensify and soil water stress is identified as one of the primary drivers of the decline of forests. While there is strong evidence of such megadisturbance in semi-arid regions, large uncertainties remain in North American temperate forests and fine-scale assessments of future soil water stress are needed to guide adaptation decisions. The objectives of this study were to i) assess the impact of climate change on the severity and duration of soil water stress in a temperate forest of eastern North America and ii) identify environmental factors driving the spatial variability of soil water stress levels. We modeled current and future soil moisture at a 1 km resolution with the Canadian Land Surface Scheme (CLASS). Despite a slight increase in precipitation during the growing season, the severity (95th percentile of absolute soil water potential) and duration (number of days where absolute soil water potential is greater than or equal to 9000 hPa) of soil water stress were projected to increase on average by 1680 hPa and 6.7 days in 80 years under RCP8.5, which correspond to a 33% and 158% increase compared to current levels. The largest increase in severity was projected to occur in areas currently experiencing short periods of soil water stress, while the largest increase in duration is rather likely to occur in areas already experiencing prolonged periods of soil water stress. Soil depth and, to a lesser extent, soil texture, were identified as the main controls of the spatial variability of projected changes in the severity and duration of soil water stress. Overall, these results highlight the need to disentangle impacts associated with an increase in the severity versus in the duration of soil water stress to guide the management of temperate forests under climate change.